Metastable marcasite NiSe2 nanodendrites on carbon fiber clothes to suppress polysulfide shuttling for high-performance lithium–sulfur batteries. Issue 39 (4th October 2021) - Wang, Jingwen; Cao, Shoufu; Yang, Likun; Zhang, Yan; Xing, Kun; Lu, Xiaoqing; Xu, Jun
Abstract : Metastable m -NiSe2 /CFC films are realized to promote chemisorption, accelerate reaction kinetics and suppress the shuttle effect of lithium polysulfides, resulting in high rate capability and superior cycling stability for lithium–sulfur batteries. Abstract : The incorporation of catalytic components is a promising strategy to promote redox reaction kinetics and suppress polysulfide shuttling for high-performance lithium–sulfur batteries (LSBs). In this work, metastable marcasite NiSe2 nanodendrites grown on carbon fiber clothes ( m -NiSe2 /CFC) were synthesized to improve chemical adsorption and electrocatalytic activity towards lithium polysulfides. The multifunctional m -NiSe2 /CFC film was utilized as both the interlayer and the three-dimensional (3D) current collector in LSBs. In comparison with the stable pyrite NiSe2 nanodendrite–covered CFC ( p -NiSe2 /CFC) counterpart, the m -NiSe2 /CFC film exhibits even stronger chemisorption, higher catalytic activity and faster reaction kinetics, thereby resulting in significantly improved lithium storage performance. The Al@S/rGO@ m -NiSe2 /CFC cell has a high reversible capacity of 1646 mA h g −1 at 0.2C, a high Q L / Q H ratio of 3.00 at 0.2C, a high rate capability of 900 mA h g −1 at 4C, and an outstanding cyclic stability exhibiting a low capacity decay of 0.028% per cycle for 600 cycles at 4C. Moreover, a symmetrically sandwiched cathode of m -NiSe2 /CFC@S/rGO@ m -NiSe2 /CFC was designed for high sulfur loading LSBs (4.5 mg cm −2 ) with superior electrochemical performance of 3.73 mA h cm −2 after 100 cycles at 1C rate. Our work opens up a new opportunity to enhance the electrochemical performance of LSBs by phase engineering of NiSe2 catalysts in sandwiched structural cathodes.